IMPLEMENTASI KEBIJAKAN INTENSIFIKASI DAN EKSTENSIFIKASI PENDAPATAN ASLI DAERAH DALAM PELAKSANAAN OTONOMI DI KOTA SURABAYA - Farida Idayati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
In monetary autonomy, Surabaya government expects to increase its province earnings. As the government regulation number 22 in 1999 (the newest is number 32 in 2004), Surabaya government has a privilege  autonomy in considering the intensification and extensification to support its province earnings for economical development. This research intends to get a real proof on implementation of intensification and extensification for province and also to get the real proof on regional economic development and the growing of earning grade after the application of newest regulation number 32 in 2004.This is a qualitative research by taking data from BPS office in Surabaya, on 10 June 2005 and from Surabaya financial department. And the results show that the new regulation can  increase the province earnings  by implementing  intensification (tax of  bill and retribution) of an area which is stated. And after the rule was issued can increase the amount of infestations. So these support the growing economic grade and infestation season around east Java regions especially in Surabaya city